2014
DOI: 10.3390/rs6076064
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Species Identification: Comparing WorldView-2 with Aerial Photographs

Abstract: Abstract:Remote sensing plays a critical role in mapping and monitoring mangroves. Aerial photographs and visual image interpretation techniques have historically been known to be the most common approach for mapping mangroves and species discrimination. However, with the availability of increased spectral resolution satellite imagery, and advances in digital image classification algorithms, there is now a potential to digitally classify mangroves to the species level. This study compares the accuracy of mangr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 38 publications
2
84
1
5
Order By: Relevance
“…The results showed that the developed rule set was able to map targeted mangrove composition objects from images with different spatial resolutions. Only limited studies have implemented the explicit hierarchical model of objects in mangrove mapping [9,12,16,69]. This study demonstrated the effectiveness of having a conceptual hierarchical model for mangrove mapping.…”
Section: Mangrove Composition Mapsmentioning
confidence: 87%
“…The results showed that the developed rule set was able to map targeted mangrove composition objects from images with different spatial resolutions. Only limited studies have implemented the explicit hierarchical model of objects in mangrove mapping [9,12,16,69]. This study demonstrated the effectiveness of having a conceptual hierarchical model for mangrove mapping.…”
Section: Mangrove Composition Mapsmentioning
confidence: 87%
“…This area is dominated by five different mangrove species: Avicennia marina, Ceriops tagal, Bruguiera exaristata, Lumnitzera racemosa and Rhizophora stylosa [21]. Other species do not represent significant coverage to be considered separately.…”
Section: Study Areamentioning
confidence: 99%
“…The spatial resolution of multispectral bands was 2.0 m, and the panchromatic band was 0.5 m. Table 1 shows the detailed spectral band description of WV2 images. WV2 images were radiometrically corrected according to the method described by Heenkenda et al [21]. First, digital numbers were converted to at-sensor-radiance values, and then, they were converted to top-of-atmosphere reflectance values.…”
Section: Remotely-sensed Data and Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies that have used highresolution satellite images for identifying and mapping coastal habitats such as coral reefs (Benfield et al, 2007), sea grass meadows (Guimarães et al, 2011), mangroves (Heenkenda et al, 2014;Ibrahim et al, 2015), macroalgae (Garcia et al, 2015;Tin, O'Leary, and Fotedar, 2015), and freshwater/ salt marsh (Carle, Wang, and Sasser, 2014). However, these studies mostly utilized sensors with fewer than four spectral bands in the visible domain, which limited the detailed classification of vegetation (Feilhauer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%